(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
After an overview of the right to mental health within the Italian legal system, the focus shifts to the protection of the right to health for irregular immigrants. It highlights how, although specific regulations are in place to safeguard this right even for those without Italian citizenship, its actual implementation remains largely inadequate. This appears to stem both from legal uncertainties and from the practical management of this right by the competent authorities. The analysis then turns to the guarantees of the right to health within the Repatriation Detention Centers, emphasizing not only the frequent denial of this right, but also the use of sedation and other restrictive practices.